Dissolution of radioactive, cesium-rich microparticles released from the Fukushima Daiichi Nuclear Power Plant in simulated lung fluid, pure-water, and seawater. (October 2019) - Suetake, Mizuki; Nakano, Yuriko; Furuki, Genki; Ikehara, Ryohei; Komiya, Tatsuki; Kurihara, Eitaro; Morooka, Kazuya; Yamasaki, Shinya; Ohnuki, Toshihiko; Horie, Kenji; Takehara, Mami; Law, Gareth T.W.; et al.
Abstract: To understand the chemical durability of highly radioactive cesium-rich microparticles (CsMPs) released from the Fukushima Daiichi Nuclear Power Plant in March 2011, we have, for the first time, performed systematic dissolution experiments with CsMPs isolated from Fukushima soils (one sample with 108 Bq and one sample with 57.8 Bq of 137 Cs) using three types of solutions: simulated lung fluid, ultrapure water, and artificial sea water, at 25 and 37 °C for 1–63 days. The 137 Cs was released rapidly within three days and then steady-state dissolution was achieved for each solution type. The steady-state 137 Cs release rate at 25 °C was determined to be 4.7 × 10 3, 1.3 × 10 3, and 1. 3 × 10 3 Bq·m −2  s −1 for simulated lung fluid, ultrapure water, and artificial sea water, respectively. This indicates that the simulated lung fluid promotes the dissolution of CsMPs. The dissolution of CsMPs is similar to that of Si-based glass and is affected by the surface moisture conditions. In addition, the Cs release from the CsMPs is constrained by the rate-limiting dissolution of silicate matrix. Based on our results, CsMPs with ∼2 Bq, which can be potentially inhaled and deposited in the alveolar region, are completely dissolved after >35 years. Further, CsMPs could remain in the environment for several decades; as such, CsMPs are important factors contributing to the long-term impacts of radioactive Cs in the environment. Graphical abstract: Image 1 Highlights: We report chemical durability of Cs-rich microparticle from Fukushima Daiichi. The dissolution rate was estimated for various solution composition. Cs-rich microparticles can remain in lung and environments for several decades.